Artificial Thermal Sensation: Stretchable Skin‐Like Cooling/Heating Device for Reconstruction of Artificial Thermal Sensation in Virtual Reality (Adv. Funct. Mater. 29/2020). (16th July 2020) - Lee, Jinwoo; Sul, Heayoun; Lee, Wonha; Pyun, Kyung Rok; Ha, Inho; Kim, Dongkwan; Park, Hyojoon; Eom, Hyeonjin; Yoon, Yeosang; Jung, Jinwook; Lee, Dongjun; Ko, Seung Hwan
Abstract : In article number 1909171, Seung Hwan Ko and co‐workers present the development of a skin‐like, highly soft, and stretchable and bi‐functional (both cold and hot sensation) thermo‐haptic device for wearable cutaneous virtual reality applications to reproduce the more realistic and fast thermal sensations on the human epidermis in a virtual world.